2008
DOI: 10.1073/pnas.0806219105
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of the human embryo requires Rac1-dependent endometrial stromal cell migration

Abstract: Failure of the human embryo to implant into the uterine wall during the early stages of pregnancy is a major cause of infertility. Implantation involves embryo apposition and adhesion to the endometrial epithelium followed by penetration through the epithelium and invasion of the embryonic trophoblast through the endometrial stroma. Although gene-knockdown studies have highlighted several molecules that are important for implantation in the mouse, the molecular mechanisms controlling implantation in the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
142
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(155 citation statements)
references
References 49 publications
(44 reference statements)
13
142
0
Order By: Relevance
“…Moreover, its coupling with TNFα-P38 signaling cascade ensures normal epithelial apoptotic elimination at postimplantation. Our findings have high clinical relevance, because Rac1 is essential for normal human endometrial-embryo dialogue as well as implantation, 23 and Ezrin has been reported to be mislocalized in the mid-secretory phase in infertile women. 63 Materials and Methods Animals and treatments.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Moreover, its coupling with TNFα-P38 signaling cascade ensures normal epithelial apoptotic elimination at postimplantation. Our findings have high clinical relevance, because Rac1 is essential for normal human endometrial-embryo dialogue as well as implantation, 23 and Ezrin has been reported to be mislocalized in the mid-secretory phase in infertile women. 63 Materials and Methods Animals and treatments.…”
Section: Discussionmentioning
confidence: 60%
“…Because Ras-related C3 botulinum toxin substrate 1 (Rac1), a small GTPase belonging to the 21 kDa Rho-GTPase family, 16,17 is a multifunctional switch involved in epithelial development, differentiation and apoptotic cell clearance in various systems, [18][19][20][21][22] and Rac1 is also involved in regulating human endometrial stromal cell migration in culture, 23 we speculated that Rac1 and its driving signaling cascade might be an important player directing normal luminal epithelial integrity conducive to on-time embryo implantation. To address this issue, in the present study, we used a uterine Rac1 conditional deletion mouse model and demonstrated that Rac1 depletion in the uterus induces premature decrease of epithelial apical-basal polarity and defective junction remodeling, hampering normal uterine receptivity and thus on-time embryo implantation.…”
mentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is known to be one potential mechanism of migration, invasion and metastasis of cancer cells including gastric cancer [32,33]. RacGAP1 regulates the function of Rho proteins such as Rac and cdc42 to influence cell morphology, cell motility, and the establishment of cell polarity and consequently plays a key role in metastasis [9,34]. Zondag et al [35] showed that the interaction between Rho and Rac GTPases and the downregulation of Rac activity led to increased Rho activity and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the majority of the genes at the core of the molecular network related to high risk of recurrence in endometrial carcinoma refer to the process of trophoblast invasion. Genes such as FOS, MMP9, MAPK1, RHOA, and TGF-b1 have been described as main directors of the process of embryo implantation (27,28). In fact, the molecular events characterizing trophoblast implantation as a physiological process of invasion into the uterus, strictly controlled both at the time and space levels, have been paralleled to the process of endometrial tumor invasion in an uncontrolled manner (29).…”
Section: Discussionmentioning
confidence: 99%